"Compassion, pleasantry, and hope": A process evaluation of a volunteer-based nonprofit. (June 2015) - Mye, Sarah C.; Moracco, Kathryn E.
Highlights: A practical, mixed-methods process evaluation of a volunteer-based nonprofit was conducted in partnership with organizational leadership. Results indicated most program components were implemented as intended, while also highlighting specific areas for improvement. From these findings, we developed a conceptual model of factors that impact quality of implementation and volunteer satisfaction: leadership, social contact, and fulfillment. Abstract: As funders continue to emphasize the importance of documented results, nonprofit organizations must work to complete program evaluations that are both valuable and feasible. The purpose of this paper is to document a practical process evaluation of a southeastern nonprofit, a local Meals on Wheels. Using a mixed methods approach, we sought to answer four evaluation questions: (1) What are the essential program components, as identified by key stakeholders; (2) To what extent are volunteers implementing the identified essential components as intended; (3) What is the level of volunteer satisfaction with the program; and (4) What suggestions do stakeholders have for improving the program? Our findings indicate that most aspects of the program were implemented as intended, but inconsistencies occurred when volunteers were unsure of their assigned duties. In addition, volunteers had high levels of satisfaction and specific suggestions for improvement. From these results, we developed a conceptual model of factors contributing to quality of implementation and volunteer satisfaction that may be generalizable to other volunteer-based nonprofits. Specifically, we identified three factors that helped to facilitate satisfaction and performance: leadership, social contact, and fulfillment. Finally, this process evaluation demonstrates the feasibility of developing and implementing evaluation tools in similar organizations.